Near-infrared spectroscopy of Cepheids in the Galactic nuclear disk. Issue Volume 9:Issue S298(2013) (6th January 2014) - Matsunaga, Noriyuki; Fukue, Kei; Kobayashi, Naoto; Ikeda, Yuji; Yamamoto, Ryo; Kyu, Shiori; Hamano, Satoshi; Yasui, Chikako; Tsujimoto, Takuji; Aoki, Wako; Nishiyama, Shogo; Nagata, Tetsuya; et al.
Abstract: We are carrying out near-infrared spectroscopy of Cepheids in the Galactic nuclear disk. The H -band spectra taken with SUBARU/IRCS indicate that their kinematics are consistent with the rotation of the nuclear disk.